Effects of Bleeder Schedule to Fiber Mass Fraction and Composites Surface Topography on Wet Lay-up Manufacturing Process - Dewi, Wiwiek Utami; Sutrisna, Rizky; Sutrisno, Sutrisno (Indonesian Journal of Aerospace, 2021)
The thermal protector materials of the rocket’s motor are made by a wet lay-up manufacturing process. Since the fiber mass fraction of the product is low, several experiments were conducted to solve this problem including changing the type of the epoxy resin and selecting the most suitable bleeder schedule. Bleeder cloth application results in increasing the fiber mass fraction. The fiber mass fraction of thermal protector material manufactured by hand lay-up can reach a maximum of 56,78%, whereas vacuum bagging can reach a maximum of 66,43%. Peel ply and breather fabric combination are the best bleeder schedule for the hand lay-up method meanwhile perforated release film and breather fabric are the best bleeders for the vacuum bagging method. Composite surface topography obtained from peel ply is visible on the surface. The imprints of the nylon peel ply weave are visible through SEM analysis. Meanwhile, the surface topography obtained from the perforated release film is not visible. The vacuum bagging method helped reduce the number of voids and ductile polymer fractures from the composite surface. This paper recommends peel ply usage in the thermal protector manufacturing process to replace the sanding or filling method that the author use nowadays.